On the Opportunity Cost of Crop Diversification. (16th May 2018) - Ang, Frederic; Mortimer, Simon M.; Areal, Francisco J.; Tiffin, Richard
Abstract: Distance functions are increasingly being augmented, with environmental goods treated as conventional outputs. A common approach to evaluate the opportunity cost of providing an environmental good is the exploitation of the distance function's dual relationship to the value function. This implies that the opportunity cost is assumed to be non‐negative. This approach also requires a convex technology set. Focusing on crop diversification for a balanced sample of 44 cereal farms in the East of England for the years 2007–2013, this paper develops a novel opportunity cost measure that does not depend on these strong assumptions. We find that the opportunity cost of crop diversification is negative for most farms.